CVM을 적용한 경인고속도로 일반화 및 선형공원 조성사업의 편익 측정 - 엄영숙; Young Sook Eom; 김상기; Sang Ke Kim (자원·환경경제연구, 2023)
본 연구는 인천광역시에서 추진하고 있는 경인고속도로 일반화 사업으로 조성될 선형공원이 제공할 여가 및 휴양 서비스 그리고 방음벽 및 옹벽 철거와 경관 개선에 따른 주거환경개선의 비시장적 편익을 조건부가치측정법(CVM)을 적용하여 측정하였다. 인천시 내 여러 구역에 걸쳐 있는 선형공원의 특성과 일반도로로 전환되지만 인근 도시 주민들 역시 통행할 수 있다는 점을 감안하여, 본 연구는 경기도와 서울시 일부지역 주민들을 잠재적 수혜자로 보고 표본에 포함하였다. 2018년 4월에 이루어진 1,000명 대상 CVM 설문조사에서 응답자들의 70%정도가 경인고속도로 일반화 사업을 긍정적으로 인식하였다. 아울러 저항응답자들을 제외한 757명의 분석표본의 50% 정도가 추가세금을 납부할 의사가 있는 것으로 나타났다. 선형공원형태의 녹지공간 조성에 찬성할수록, 그리고 본 사업이 주변 주거환경 개선에 도움이 될 것이라고 생각하는 응답자들일수록 추가세금 납부를 긍정적으로 평가하였다. 경인고속도로 일반화 사업을 위한 연간 지불의사 평균은 인천시 거주자들이 15,300원 정도, 그리고 수도권 거주자들이 6,800원 정도로 측정되었다. 본 사업의 간접영향권이라고 볼 수 있는 수도권 거주자들도 본 사업을 위해 상당한 금액을 지불할 의사가 있는 것으로 나타났다. This study applied the contingent valuation method (CVM) to measure the benefits from an urban liner park that will be created as part of the Gyeongin Expressway downgrade project by Inchon metropolitan city government. The Incheon city government plans to create a liner park (10.5 km) in the middle of the downgraded road to provide leisure and recreation services to residents, and plans to remove retaining walls and soundproof walls to improve the urban residential environment. Considering the characteristics of a liner park that spans several districts in Incheon city and the downgraded road that will be passed by residents of nearby cities as well as Incheon residents, the target population included residents of part of Seoul and several cities surrounding Incheon. In a CVM survey of 1,000 respondents conducted in April 2018, about 70% of the respondents perceived this project positively. About 50% of 757 respondents, excluding protest bids respondents, were willing to pay additional taxes for this project. The more the respondents favored the creation of a linear park and the more they thought that this project would improve the surrounding residential environment, the more positively they evaluated the additional tax payment. The average annual willingness to pay for this project was about 15,300 won for Incheon residents and 6,800 won for residents of Seoul metropolitan area. It is interesting to observe that residents of Seoul metropolitan area, who are not directly affected by this project, were willing to pay a considerable amount for this project.